Survival of double-crown-retained dentures either tooth-implant or solely implant-supported: an 8-year retrospective study - Kappel, Stefanie; Bernhart, Gunda; Hassel, Alexander J.; Rammelsberg, Peter (Clinical implant dentistry and related research, 2012)
Purpose To compare survival and incidence of complications for solely implant-supported double-crown-retained dentures (DCRDs) and combined tooth-implant-supported DCRDs for restoration of a complete jaw. Materials and Methods Patients were consecutively admitted to treatment at the Department of Prosthodontics, University of Heidelberg, during a time period from 2003 to 2011. Schedule and unscheduled visits were recorded on standardized documentation forms. Age, gender, location of implants, number of abutment teeth, jaw, and antagonist were assessed as possible factors affecting the number of complications per patient. Results Fifty-five patients with 66 DCRDs on 209 implants and 102 teeth were included. Of these, 30 dentures on 129 implants were solely implant-supported whereas the other 36 were combined tooth-implant-supported. During an observation period of up to 8.3 years (mean 3.4 years; SD 1.9) superstructure survival was 93.3% for the solely implant-supported DCRDs and 100% for the combined tooth-implant-supported DCRDs. Survival without major complications was 86.7% and 83.3%, respectively. Gender and location of both superstructure and implants were statistically associated with a greater number of complications. Conclusion Within the limitations of this exploratory retrospective study, not only solely implant-supported DCRDs but also superstructures combining remaining teeth and implants within DCRDs might be a reliable treatment option for elderly patients. Prospective randomized clinical trials are needed to confirm this, however.